2013
DOI: 10.5414/cn107926
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in revealing complications following percutaneous renal biopsy in children

Abstract: Age ≥ 10 is an independent risk factor for post-PRB complication. After the procedure, the formation of a large hematoma predicted a complicated clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…One study by Shah et al (25) included fresh frozen plasma administration in addition to blood administration; all other studies reported only blood transfusion. Given that multiple studies included a blood transfusion event of zero (4,7,17,19,20,(22)(23)(24)26,27), a continuity correction of 0.5 was added to counts of zero to both event and nonevent rates for the purposes of this analysis. These 23 studies included 5504 total biopsies.…”
Section: Development Of Perinephric Hematoma Postbiopsymentioning
confidence: 99%
“…One study by Shah et al (25) included fresh frozen plasma administration in addition to blood administration; all other studies reported only blood transfusion. Given that multiple studies included a blood transfusion event of zero (4,7,17,19,20,(22)(23)(24)26,27), a continuity correction of 0.5 was added to counts of zero to both event and nonevent rates for the purposes of this analysis. These 23 studies included 5504 total biopsies.…”
Section: Development Of Perinephric Hematoma Postbiopsymentioning
confidence: 99%
“…Several researches have proposed that post-biopsy ultrasound could be used to exclude the presence of complications [5,6]. One research has found that inpatient status and thrombocytopenia were the only significant risk factors for the complications [7].…”
Section: Introductionmentioning
confidence: 99%
“…Between April 2014 and January 2018, a total of 244 biopsies of native kidney were performed at Saitama Children's Medical Center. All biopsies, guided using real‐time ultrasonography, were performed by pediatric nephrologists with a 16 G automated spring‐loaded biopsy needle . Post‐biopsy ultrasonography showed peri‐renal hematoma in 99 patients (49 boys, 50 girls; median age, 9.0 years).…”
Section: Prb Subject Characteristics Vs Use Of Pslmentioning
confidence: 99%
“…All biopsies, guided using real-time ultrasonography, were performed by pediatric nephrologists with a 16 G automated spring-loaded biopsy needle. 2 Post-biopsy ultrasonography showed peri-renal hematoma in 99 patients (49 boys, 50 girls; median age, 9.0 years). Peri-renal hematomas were classified according to size, as previously reported: 3 small, ≤1/3 of maximum length of the biopsied kidney; and large, >1/3 of maximum length of the biopsied kidney.…”
mentioning
confidence: 98%